2018
DOI: 10.1139/cjpp-2017-0577
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Frizzled receptors and their co-receptors in calcified human aortic valves

Abstract: The cellular mechanisms that induce calcific aortic stenosis are yet to be unraveled. Wnt signaling is increasingly being considered as a major player in the disease process. However, the presence of Wnt Frizzled (Fzd) receptors and co-receptors LRP5 and 6 in normal and diseased human aortic valves remains to be elucidated. Immunohistochemistry and quantitative polymerase chain reaction were used to determine Fzd receptor expression in normal and calcified human aortic valve tissue, as well as human aortic val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Moreover, the ligands stimulate VICs, apoptosis and calcium deposits ( 99 ). Abundant expression of Fzd receptors and co-receptors Lrp5/6 also suggest the involvement of canonical Wnt/β-catenin signaling in CAVD ( 81 , 100 ). In vitro , Wnt treatment of VICs inhibit chondrogenic differentiation and promote osteogenic gene expression ( 101 , 102 ) while Lrp5/6 is required to promote calcification in hypercholesterolemia mouse model ( 103 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ligands stimulate VICs, apoptosis and calcium deposits ( 99 ). Abundant expression of Fzd receptors and co-receptors Lrp5/6 also suggest the involvement of canonical Wnt/β-catenin signaling in CAVD ( 81 , 100 ). In vitro , Wnt treatment of VICs inhibit chondrogenic differentiation and promote osteogenic gene expression ( 101 , 102 ) while Lrp5/6 is required to promote calcification in hypercholesterolemia mouse model ( 103 ).…”
Section: Introductionmentioning
confidence: 99%
“…nals, LRP6 restrains noncanonical signaling programs in VSM that promote cardiovascular calcification (9), arteriosclerotic stiffening (9), and neointima formation (14) in mice. Similar noncanonical Wnt signals participate in aortic valve calcification as well (15,16). Thus, human genetics and murine molecular genetics have converged to firmly place Wnt/LRP6 signaling as a key component of cardiometabolic disease, including arteriosclerosis.…”
mentioning
confidence: 99%
“…Our lab has previously demonstrated that several non-canonical Wnt ligands are present in AVS patients and promote calcification and apoptosis in HAVICs ( Albanese et al, 2017 ). Additionally, we showed that the mRNA and protein expression of frizzled receptors and their co-receptors are upregulated in AVS patients ( Siddique et al, 2017 ). Accordingly, interest in the modulators by which Wnt signaling is regulated is growingly ignited.…”
Section: Discussionmentioning
confidence: 93%
“…Aortic valve interstitial cells (VICs) treated with these Wnt ligands exhibited significant apoptosis and enhanced calcification (Albanese et al, 2016b). This likely to be mediated through frizzled and LRP5/6 co-receptor activation in calcified aortic valve leaflets, which play overlapping roles in Wnt/β-catenin signaling (Siddique et al, 2017). Interestingly, Wnt-signaling appears to play similar pathogenic and pro-calcific roles in multiple cell types during AVS development including HAVICs (Fang et al, 2018), endothelial cells (Masckauchán et al, 2005) and macrophages (Blumenthal, 2006).…”
Section: Introductionmentioning
confidence: 99%